In Situ Determination of the Transport Properties of Near-Surface Concrete Using AC Impedance Spectroscopy Techniques - Lipeng Wu; Peng Dai; Yong Li (Journal of Engineering)
The durability of existing concrete structures has increasingly attracted widespread attention in recent years. The phenomenon of performance degradation is often associated with the intrusion of hazardous ions from outside. As the first barrier to external substances intrusion, the near-surface concrete plays an important role in durability. So the performance of in-service concrete structures often depends on the transport properties of the near-surface concrete. Accordingly, information on service conditions and life prediction can be obtained by testing these transport properties. In this paper, an in situ method for chloride ion diffusion coefficient determination is proposed based on the relationship between the alternating current impedance spectroscopy parameters and the chloride ion diffusion coefficient. By a rational design, the new method can synthetically reflect the transport properties of near-surface concrete and is not affected by the presence of the reinforcing bar. In addition, the experimental results show that the method is in good agreement with “PERMIT” migration test which has been widely used. The proposed method is less time consuming and nondestructive and has good reproducibility.